Adenosine Deaminase‐Like Gene‐Carried Lentivirus Toolkit for Identification of DNA N6‐Methyladenine Origins - Ziyu Liang; Shaokun Chen; Yao Li; Weiyi Lai; Hailin Wang (Advanced Science)
Abstract Post‐replicative DNA N6‐methyladenine (pr6mdA) can form via bona fide methylase‐catalyzed adenine methylation, playing a pivotal role in embryonic development and other biological processes. Surprisingly, pre‐methylated adenine can be erroneously incorporated into DNA as misincorporated N6‐methyladenine (i6mdA) via DNA polymerase‐mediated replication. Despite pr6mdA and i6mdA sharing identical chemical structures, their biological functions diverge significantly, presenting a substantial challenge in distinguishing between the two. Here, for the first‐time, it is exploited that the adenosine deaminase‐like (Adal) protein and a corresponding activity‐null mutant to construct an Adal lentivirus toolkit. With this newly designed toolkit, both pr6mdA and i6mdA can be identified and quantified simultaneously. The presence of 6mdA in the bone marrow cells of mice is shown, with its levels serving as indicators for growth with age, probably reflecting the cellular stress‐caused changes in RNA decay, nucleotide pool sanitation, and transcription. Collectively, a powerful toolkit to advance understanding of both pr6mdA and i6mdA is demonstrated.